Hildebrand, moral disagreement, and the concept of “morality” - Gamache, Joseph (International journal of philosophy and theology, 2024)
This paper investigates and raises several criticisms of Dietrich von Hildebrand’s account of moral disagreement in terms of the phenomenon of moral value blindness. In an effort to vindicate Hildebrand’s account, the paper examines his distinction between moral (and morally-relevant) values and non-moral (non-morally-relevant) values – a distinction the working-out of which Hildebrand declared to be a ‘fundamental task’ for ethics. The implications of Hildebrand’s theory of ‘morality’ for deliberation and moral rigorism are then discussed. The conclusion of these investigations is that Hildebrand’s account of moral disagreement renders his account of moral knowledge unsuitable for those disinclined to moral theology, and therefore of limited value as part of a purely philosophical account of moral knowledge. The paper ends positively by sketching what Hildebrandian ethics might look like without Hildebrand’s notion of the ‘moral.’